Salivary hormones, IgA, and performance during intense training and tapering in judo athletes - Papacosta, E.; Gleeson, M.; Nassis, G. P. (The Journal of Strength and Conditioning Research, 2013)
The aims of this study were to identify the time course of change of salivary testosterone (sT), cortisol (sC), and IgA (SIgA); mood state; and performance capacity during a 2-week taper in judo athletes and to examine the diurnal variation in these salivary markers. Eleven male judo athletes completed 5 weeks of training: 1 week of normal training (NORM), 2 weeks of intensified training (INT), and 2 weeks of exponential tapering (TAPER). Once per week subjects completed vertical and horizontal countermovement jump tests, a grip strength test, a Special Judo Fitness Test, a multistage aerobic fitness test, a 3 × 300-m run test, and anthropometric measurement. Subjects also completed questionnaires to assess mood state and muscle soreness. Two daily saliva samples (at 0700 and 1900) were collected at the end of each week during NORM and INT and every day during TAPER. Increased morning sT, decreased evening sC, lower muscle soreness, and enhanced mood state (p < 0.05) were evident by the early phases of TAPER. A significant 7.0% improvement in 3 × 300-m performance time, a 6.9% improvement in the vertical jump (p < 0.05), and increased morning and evening SIgA secretion rate (p < 0.01) were observed during the middle-late phases of TAPER. The higher values of salivary variables were observed in the morning. This study indicates that salivary hormones display diurnal variation. Furthermore, changes in hormonal responses, mood state, and muscle soreness precede enhancements in performance and mucosal immunity, suggesting that judo athletes taper for at least a week before competition.